Acompanhamento da gestação em cadelas pelo exame ultrassonográfico: revisão de literatura - Castro, Viviane Montich de [UNESP] (2011)
The ultrasonography exam is largely used in Veterinary Medicine as a method of diagnosis on several domestic animals species, mainly to diagnose pregnancy. Beyond confirm the pregnancy, the ultrasound is able to assess the age of the fetus, the conditions of the ovary and the uterus, the structures and vital condition of the fetus and the fetal development on different pregnancy s stages. The ultrasound has 94% of precision to diagnosis pregnancy since the 30º day after the breed. Compared with the humans being, the application of the ultrasound to estimate the fetal age in bitch is limited, due to the large variation of breed and size on this specie. Several formulas were developed to calculate the gestational age and to provide the date of the birth in dogs, but it is unknown the efficacy of this formulas on the different gestational stages and on different breed of dogs. Therefore, new studies are necessary to guide the veterinary about the best choice of the ultrasonographic evaluation method to known exactly the date of the gestational age.